Did PLAs on LA affordable housing projects raise construction costs? - Peter Philips; Scott Littlehale (The University of Utah, Department of Economics, 2015)
The cost of building nine affordable housing projects in Los Angeles under the terms of a project labor agreement between the years 2008 and 2012 are compared to 121 affordable housing projects developed and built in the same time period and same area without project labor agreement requirements. We use three approaches to compare costs: 1) simple comparison of average square foot cost and average per unit cost, 2) a visual inspection of the cost data by increasing size of projects measured by square foot size and housing unit size, and 3) "nearest neighbor" analysis comparing the nine PLAs each to the four nearest comparisons along the dimensions of size, units, stories and targeted population. We break our sample down into a subsample for the City of Los Angeles excluding within-county but outside-the-city projects and into a subsample for prevailing wage projects only. Our conclusions are the same using all three statistical approaches to comparing costs and using all three samples: the nine PLA affordable housing projects were not more expensive to build than comparable projects not governed by project labor agreements.
Keywords: J41; J45; J48; J58; R28; J5; 330; project labor agreements; affordable housing